General characteristics of crime in the customs sphere - Rohatynska, Nina (Actual problems of law (Aktual’ni problemi pravoznavstva), 2022)
The article analyzes the crime in the customs sphere as a negative phenomenon and identifies the most effective measures of general social prevention. The essence of the concept of "customs crime" is defined, which is interpreted primarily through the main directions of criminal policy of the state, and secondly - the understanding of the components of its customs policy. The implementation of customs policy is a constant task of the state and its impact on public relations in the country is unpredictable, because it under the pressure of objective and subjective circumstances can dramatically change their orientations, as well as forms, methods and measures to achieve them. In the course of the research it was recognized that crime in the customs sphere in its essence causes great damage to the financial and credit system in the country, affects foreign economic activity, fuel and energy sphere, and also caused tens of billions of hryvnias to the state budget. . Special signs of customs crime have been identified. Attention should also be paid to the organizational factors of crime in the customs sphere: the lack of a state system of criminological monitoring of the economy as a whole. Low level of coordination of law enforcement agencies to prevent crime in the customs sphere. Lack of a highly effective mechanism for searching abroad and returning illegally exported property. It has been proven that today customs violations are an integral part of economic crime, which is closely linked to the functioning of the "shadow" economy, embezlement, evasion of customs duties and taxes, malfeasance, corruption. It should be noted that the complication of financial schemes to carry out illegal customs operations has led to the predominance of group forms of this crime, which, according to the Criminal Code of Ukraine, is punished more severely.The necessity of institutional reorganization of the system of criminal justice bodies and introduction of new forms and methods of their activity in the fight against criminal offenses in the customs sphere is substantiated. The results of the study can be used in lawmaking and law enforcement activities in the investigation of criminal offenses related to corruption in the customs sphere.